Ukraine : Country Procurement Assessment Report 2006 - World Bank (Washington, DC, 2012)
Ukraine enacted a comprehensive Public Procurement Law (PPL) on February 22, 2000. The first World Bank Country Procurement Assessment Report (CPAR) for Ukraine finalized in November 2001 included an action plan for improving systemic efficiency of public procurement. Since the 2001 CPAR, the country has undergone numerous political and economic changes with natural concurrent evolution of the public procurement system. In light of these changes, the Government and the World Bank jointly undertook the present review of the legal and regulatory framework for procurement, institutional capacities, actual practice, and the integrity of the system as a whole. The analysis and main findings of this report are presented as follows: Section 2 analyzes the legislative and regulatory framework of late 2005 through this writing in 2006. Section 3 analyzes institutional framework and management capacity. Section 4 covers procurement operations, including functionality of the public procurement market, contract administration, and provisions for dispute resolution. The report then discusses integrity and transparency of the system (Section 5), e-procurement (Section 6), public procurement contract performance (Section 7), and gradual harmonization with the EU directives and eventual accession to the WTO (Section 8). Section 9 presents risk analysis and the 2006 action plan. Key recommendations are summarized in Section 9 and repeated in the executive summary.